Development of research of low-dimension metal-containing systems from P.P. Weymarn to our days - I. V. Pleskunov; A. G. Syrkov (Записки Горного института, 2018)
The article analyzes main laws discovered by P.P.Weymarn (1879-1935) during his work at the Saint-Petersburg Mining University, they are connected with obtaining metal-containing disperse substances with nanometer particle size. It enlists priority papers in this field (1906-1915) and describes peculiarities of P.P.Weymarn scientific school which has several connections to modern research being conducted at the Saint-Petersburg Mining University in the field of «nanotechnology» as well as by foreign scientists. The paper reveals continuity in the field of several objects (disperse metals) and the methodology of studying the properties and stoichiometry of substances depending on dispersity. It provides information on achievements in synthesis of surface nanostructured metals and low-dimension forms of substances in various porous matrixes. Among the studies of the XXI century developing Weymarn’s ideas there can be noted solid-state hydride synthesis of metals, layering of different-sized molecules of ammonium compounds on metals (Al, Cu, Ni, Fe), as well as synthesis of metal nanostructures (Ag, Cu, Bi) using porous glass as a particle size stabilizing matrix. In the latter case, the dispersity of the metal increases while its melting point decreases.